Alliances and Return Predictability. (16th December 2016) - Cao, Jie; Chordia, Tarun; Lin, Chen
Abstract : Building on the growing literature on interfirm links and limited attention, we find evidence of return predictability across alliance partners. A long–short portfolio sorted on lagged returns of strategic alliance partners provides a return of 89 basis points per month that is robust to a number of specifications. Investor inattention and limits to arbitrage may be the source of the underreaction of a firm's returns to that of its partners.